A Shared Vision Begets the Future: Korea-India Defense Cooperation - YEON-JUNG JI (The Journal of Indian and Asian Studies, 2023)
For the past two decades, India and South Korea have sought to create a strategic convergence in their long-term cooperation. Defense cooperation, which has been discussed bilaterally, is a key area of their partnership, should it later be transformed to companionship. As some of their efforts have materialized, South Korea has become the fifth largest exporter of conventional arms to India. Markedly, Seoul and New Delhi are on the way to restyle their regional strategies towards each other to fit into their Indo-Pacific strategies. In the course, two sides have found valid points to explore stronger partnership than in the past. The stronger driver they have now is likely to sustain in the future as they already made some meaningful progress in the last decade. In this latest move, the two sides appear to be on the right trajectory; however, the future awaits a more productive joint effort.